Efficacy and Safety of Individualized Schedule of Sunitinib by Drug Monitoring in Patients with Metastatic Renal Cell Carcinoma - Zhu X; Zhang X; Sun G; Liu Z; Zhang H; Yang Y; Ni Y; Dai J; Zhu S; Chen J; Zhao J; Wang Z; et al. (Cancer Management and Research, 2021)
Xudong Zhu,1,2,* Xingming Zhang,1,2,* Guangxi Sun,1,2,* Zhenhua Liu,1,2,* Haoran Zhang,1,2 Yaojing Yang,1,2 Yuchao Ni,1,2 Jindong Dai,1,2 Sha Zhu,1,2 Junru Chen,1,2 Jinge Zhao,1,2 Zhipeng Wang,1,2 Hao Zeng,1,2 Pengfei Shen1,2 1Department of Urology, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 2Institute of Urology, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengfei ShenDepartment of Urology, West China Hospital, Sichuan University, No. 37 Guoxue Xiang, Chengdu, 610041, Sichuan, People’s Republic of ChinaEmail cdhx510@163.comHao ZengDepartment of Urology, West China Hospital, Sichuan University, No. 37 Guoxue Xiang, Chengdu, 610041, Sichuan, People’s Republic of ChinaEmail kucaizeng@163.comPurpose: To investigate the survival benefit and safety of individualized schedules for sunitinib in patients with metastatic renal cell carcinoma (mRCC) through plasma concentration monitoring.Methods: A total of 105 patients with mRCC were enrolled. The schedule was adjusted in two ways: therapeutic drug monitoring (TDM) and toxicity-adjusted schedule (TAS). One group of patients were without any schedule adjustment (maintained schedule, MAS). Progression-free survival (PFS), overall survival (OS), tumor response, and adverse events (AEs) were compared. The relationship between AEs and steady-state concentration or consecutive monitoring curves was explored. Further monitoring of individualized schedules was also conducted.Results: Based on the plasma concentration, the schedules of 18 patients were adjusted in the TDM group. The schedules were adjusted in 37 patients due to severe AEs in the TAS group, while 50 patients were without any schedule adjustment. The median PFS and OS were better in the TDM group than the other two groups (p = 0.001 and p = 0.004, respectively). Univariate and multivariate analyses indicated that TDM could decrease the risk of death independently (p = 0.026). Moreover, the incidence of grades 3/4 AEs decreased from 88.9% to 33.3% in the TDM group (p = 0.001). Sunitinib concentration in  150– 200ng/mL was regarded as a “transitional zone” due to severe AEs mainly happened when concentration elevated over it. After TDM, further plasma concentration monitoring indicated that individualized schedules enabled sunitinib concentration to fluctuate in a much safer range.Conclusion: Treatment-related toxicities could be minimized through plasma concentration monitoring. Patients with adjusted schedules by therapeutic drug monitoring could achieve better survival benefits.Keywords: sunitinib, plasma concentration, metastatic renal cell carcinoma, individualized schedule adjustment, clinical outcomes